2023
DOI: 10.1021/jasms.3c00158
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Lipidomic Characterization of Meningioma Grades Using LC–HRMS and Machine Learning

Hoda Safari Yazd,
Sina Feizbakhsh Bazargani,
Garrett Fitzpatrick
et al.

Abstract: Meningiomas are among the most common brain tumors that arise from the leptomeningeal cover of the brain and spinal cord and account for around 37% of all central nervous system tumors. According to the World Health Organization, meningiomas are classified into three histological subtypes: benign, atypical, and anaplastic. Sometimes, meningiomas with a histological diagnosis of benign tumors show clinical characteristics and behavior of aggressive tumors. In this study, we examined the metabolomic and lipidomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Promising preliminary data suggests that meningioma grades can be partially differentiated based on MRM-MS2 12 C/ 13 C area ratios acquired with TRAM (Supporting Information Figure S9). These preliminary findings indicate that LC-MS-based metabolomics can not only be applied to tumor tissue samples, as already described in literature [31][32][33] , but also to CSF collected from patients. Future studies with larger cohorts and different brain tumor subtypes will further explore this potential and could find metabolite patterns for which intraoperative diagnostics by sensors can be envisaged combined with methylation profiles.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Promising preliminary data suggests that meningioma grades can be partially differentiated based on MRM-MS2 12 C/ 13 C area ratios acquired with TRAM (Supporting Information Figure S9). These preliminary findings indicate that LC-MS-based metabolomics can not only be applied to tumor tissue samples, as already described in literature [31][32][33] , but also to CSF collected from patients. Future studies with larger cohorts and different brain tumor subtypes will further explore this potential and could find metabolite patterns for which intraoperative diagnostics by sensors can be envisaged combined with methylation profiles.…”
Section: Resultssupporting
confidence: 74%
“…The meningioma grade could be distinguished based on metabolic pathways such as glycine/serine metabolism, choline/tryptophan, purine and pyrimidine metabolism. 31 The same study revealed an additional set of changing metabolites by unsupervised statistical analysis. Taurine, creatine, serine, choline, thiamine, phenylalanine, biotin, glutamine, and arginine were proposed as signature metabolites by hierarchical clustering.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations